Evaluation of parietal pleural invasion of lung cancers with breathhold inspiration and expiration MRI - (:unkn) unknown (My University, 1999)
The goal of this study was to investigate the feasibility of detecting invasion of the parietal pleura by lung cancer with inspiratory-expiratory magnetic resonance imaging (MRI). Twenty-three patients with lung cancer in contact with pleura were studied with multisectional MRI during deep inspiration and expiration on the axial and coronal planes. Changes in the tumor's relation relative to the chest wall markers, vertebral bodies, or mediastinal structures were noted. Surgical correlation was available for each case. Twelve tumors were located at the right middle and lower lobes. Five patients who had a significant change in the position of the tumor were found not to have pleural invasion at surgery. The remaining seven tumors without change in their position with respiration were surgically found to invade the parietal pleura. Only 1 of the 11 upper lobe and apical segments of the lower lobe-located tumors showed a change in its position, which had no parietal pleural invasion at surgery. The remaining 10 tumors did not show any movement. Four of them had parietal pleural invasion that were surgically proven, and six tumors had no parietal pleural invasion at surgery. In conclusion, MRI performed during deep inspiration and expiration is a complementary method in detecting parietal pleural invasion for the tumors located in the lower and middle lobes.
Keywords: Female; Humans; Middle Aged; Aged; Male; Magnetic Resonance Imaging; Contrast Media; Prospective Studies; Respiration; Neoplasm Invasiveness; Lung Neoplasms; Pleural Neoplasms